Plasma dopa decarboxylase activity in treatment-resistant recent-onset psychosis patients. (September 2019) - van der Pluijm, Marieke; Sutterland, Arjen L.; van Kuilenburg, André B. P.; Zoetekouw, Lida; de Haan, Lieuwe; Booij, Jan; van de Giessen, Elsmarieke
Treatment resistance (TR) in psychosis is a major clinical problem. A biomarker predicting TR against conventional antipsychotic drugs would be relevant, potentially reducing unnecessary delay to adequate treatment with clozapine. Dopa decarboxylase (DDC) activity in the striatum, measured with positron emission tomography, is elevated in responders, but not in treatment-resistant patients. Plasma DDC activity could be a surrogate marker for DDC brain activity, and thus a potential biomarker that could be used in daily clinical practice. Therefore, we determined plasma DDC activity in 40 male patients with recent-onset psychosis, of whom the majority had started treatment, whereby 21 turned out to be treatment responders and 19 treatment resistant during follow up. We observed no significant group differences. Furthermore, symptom severity was not associated with plasma DCC activity. We did observe a trend level difference in the distribution of plasma DDC activity across categories of medication, with subsequent post hoc analysis showing lower DDC activity in risperidone-using patients. This may suggest that risperidone could influence plasma DDC activity. Based on these results, plasma DDC activity does not appear to be a promising biomarker for TR in recent-onset psychosis patients who are already receiving antipsychotic treatment.